Bear on the loose! - Lysiak, Hilde, 2006-; Lysiak, Matthew; Lew-Vriethoff, Joanne (New York, NY : Branches/Scholastic Inc., 2017)
When she hears reports of bear roaming the backyards of Selinsgrove, Hilde and her sister/photographer Izzy are determined to get the story for their own newspaper, the Orange Street News--but when they find out the culprit is a black bear cub, their scoop turns into a rescue mission.
Appeals to 2nd-3rd graders.
Reading level grade 2.
Keywords: Lysiak, Hilde, -- 2006- -- Juvenile fiction; Reporters and reporting -- Juvenile fiction; Black bear -- Juvenile fiction; Wildlife rescue -- Juvenile fiction; Sisters -- Juvenile fiction; Detective and mystery stories; Mystery and detective stories; Reporters and reporting -- Fiction; Black bear -- Fiction; Bears -- Fiction; Wildlife rescue -- Fiction; Sisters -- Fiction; Mystery fiction; Detective and mystery fiction